Helicobacter pylori infection in children - Yvan Vandenplas (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2000)
Helicobacter pylori colonizes the stomach of man, especially during childhood. However, H. pylori strains are not created equal, with major differences in virulence factors such as the vacuolating cytotoxin A and the cytotoxic-associated gene A, probably accounting for different clinical symptoms. The majority of infected subjects remain asymptomatic. Symptoms are aspecific. Helicobacter pylori infection is correlated with socioeconomic conditions and hygienic circumstances, resulting in an extremely high prevalence in children in developing countries. The golden standard technique to diagnose Helicobacter infection is culture of gastric biopsies; specificity and sensitivity of serology are low during childhood. Carbon-13 urea breath tests are a useful in the diagnosis but especially during follow-up. Recommended treatment consists of proton pump inhibitors in combination with two antibiotics out of amoxycillin, clarithromycin and metronidazole. The importance or clinical relevance of Helicobacter infection in asymptomatic individuals remains to be determined.Key words: Helicobacter pylori, gastritis